FRI0681 Clinical validation studies of the 2012 classification criteria for early rheumatoid arthritis (ERA) in a domestic multi-center cohort. (15th June 2017) - Li, Y; Fan, W; Chen, H; Yu, P; Miao, H; Li, K; Xu, J; Cui, L; Zhang, G; Xu, K; Zhang, L; Li, R
Abstract : Background: Recently, a new classification criteria for early rheumatoid arthritis (ERA) have been developed. Objectives: To evaluate the value of 2012 classification criteria for early rheumatoid arthritis (ERA), 2010 ACR/EULAR classification criteria, and 1987 ACR classification criteria in the diagnosis of early RA. Methods: Early arthritis patients with age more than 16 years, disease duration no more than 1 year, Cat least one joint swelling and tenderness were enrolled in a multicenter, open, cross-sectional study cohort. The patients were diagnosed as RA or other none RA disease by 2 trained experienced rheumatologists. Detailed recorded the clinical and laboratory parameters include disease duration, morning stiffness duration, RF, anti-CCP, ESR, CRP etc.The sensitivity and specificity of three RA classification criteria were compared by McNemar test, The areas under the ROC curve (AUC) of each RA classification criteria were analyzed using MedCalc software. Results: A total of 310 patients were randomly enrolled in this study, including 182 ERA and 128 non-RA. The sensitivity (88.5%) of ERA criteria were much higher than that of 1987 ACR criteria (45.6%, χ 2 =75.013, P <0.0125), and not significantly different with the 2010 ACR/EULAR criteria (91.8%, χ 2 =1.042, P >0.05). The specificity of ERA criteria (91.4%) were similar to those of 2010 ACR/EULAR criteria (87.5%, χ 2 =1.8, P >0.05) and 1987 ACR criteria (96.1%, χ 2 =3.1, P >0.05). The AUC of ERA criteria was 0.962 (95% CI: 0.934, 0.980), which was slightly better than that of the 2010 ACR/EULAR criteria [0.959 (95% CI: 0.931, 0.978), Z =0.380, P =0.7038], and much higher than that of the 1987 ACR criteria [0.885 (95% CI: 0.845, 0.919), Z =4.517, P <0.0001]. Conclusions: Overall evaluation, the diagnostic value of ERA criteria is better than 1987 ACR and 2010 ACR/EULAR criteria in early rheumatoid arthritis. Compared to 2010 ACR/EULAR classification criteria, ERA criteria is obviously more simple and practical. References: Li R, Sun J, Ren LM, et al. Epidemiology of eight common rheumatic diseases in China: a large-scale cross-sectional survey in Beijing[J]. Rheumatology, 2012, 51(4): 721–729. Radner H, Neogi T, Smolen JS, et a1. Performance of the 2010 ACR/EULAR classification criteria for rheumatoid arthritis: a systematic literature review[J]. Ann Rheum Dis, 2014, 73(1): 114–123. Cader MZ, Filer A, Hazlehurst J, et al. Performance of the 2010 ACR/EULAR criteria for rheumatoid arthritis: comparison with 1987 ACR criteria in a very early synovitis cohort[J]. Ann Rheum Dis, 2011, 70(6): 949–955. Ye H, Su Y, Li R, et al. Comparison of three classification criteria of rheumatoid arthritis in an inception early arthritis cohort[J]. Clinical Rheumatology, 2016, 35(10): 2397–401. Zhao JX, Su Y, Liu XY. et al. Classification criteria of early rheumatoid arthritis and validation of its performance in a multi-centre cohort[J]. Clinical and Experimental Rheumatology, 2014, 32(5): 667–673. Disclosure of Interest: None declared